Microbiological Profile and Clinical Outcomes of Febrile Neutropenia in Cancer Patients at a Tertiary Care Centre in Nepal - Thapa, Pradeep; Shilpakar, Ramila; Acharya, Bibek; Chapagain, Sandhya; Poudyal, Saugat; Thapa, Sudip; Pandey, Shama; Gurung, Jasmine; Paudel, Bishnu Dutta (Annapurna Journal of Health Sciences, 2025)
Introduction: Febrile Neutropenia (FN) from chemotherapy raises mortality (10%) and healthcare burden. Immediate broad-spectrum antibiotics are vital, highlighting the importance of personalized antibiotic choices for FN. Methods: This prospective observational study, conducted at Bir Hospital and Bhaktapur Cancer Hospital from 2023 to 2024, investigated 200 cases of chemotherapy-induced febrile neutropenia. From the patients with chemotherapy induced febrile neutropenia, blood and relevant samples were cultured for antibiotic sensitivity. Initial antibiotic therapy followed Infectious Diseases Society of America guidelines (IDSA), later adjusted based on cultures. Granulocyte colony-stimulating factor was used until neutrophil recovery. Outcomes, including mortality and hospital stay, were recorded. Analysis, using Statistical Package for the Social Sciences (SPSS), considered various factors presenting results as mean ± standard deviation or frequency and percentage and significance at P<0.05, using T-test and Fisher’s-exact test. Results: Among 200 cases of febrile neutropenia with mean age of 49.41 years, only 2.5% had severe neutropenia. Cultures were positive in 9.5% cases primarily from blood (42.1%) and urine (15.8%) with predominance of Gram-negative bacteria (Escherichia coli and Klebsiella). Most bacterial isolates were sensitive to antibiotics like amikacin, tazobactam-piperacillin, imipenem, and meropenem, tigecycline and resistance to oral ciprofloxacin and cefotaxime was in significant number of cases. The mean hospital stay was 5.82 days and only 4 deaths were recorded. Advanced age and comorbidities correlated with increased mortality rates. Conclusion: Timely empirical antibiotics reduce mortality in febrile neutropenia and should be customized according to local pathogen and sensitivity patterns. Advanced age and comorbidities are linked to increased mortality thus require careful management.